Stroke survivors', without aphasia, perceptions on their involvement as research partners : a thematic analysis - Triantafyllidou, Ioanna (q, 2021)
This study aimed to investigate the views of stroke survivors and people with aphasia (PWA) about their involvement as research partners in PPI studies. Semi-structured interviews were conducted in this study. Eight stroke survivors were recruited, four with aphasia and four without. A thematic analysis was performed for the qualitative analysis of the data. Four main themes were identified: Restrictions, Support, Involvement and Impact. Subsequently, all subthemes were implemented on the ICF framework of the World Health Organization (WHO, 2003). In this study we suggest the addition of a new domain on the ICF framework, the "Quality of Life- QOL" domain to illustrate the dynamic relationship between the effects of stroke in all domains and how these factors influence people with aphasia and stroke survivors in general to be actively involved as research partners. In conclusion, stroke survivors, with or without aphasia, concluded that they wish be involved in stroke and aphasia related research with the necessary support and contribute to both science and the stroke survivors’ community.
Keywords: Stroke survivors; People with Aphasia; Quality of life; PPI; Thematic analysis